2018
DOI: 10.1002/aenm.201801501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crystal Orientation and Conduction Band Grading of Absorber on Efficiency of Cu(In,Ga)Se2 Solar Cells Grown on Flexible Polyimide Foil at Low Temperature

Abstract: Flexible Cu(In,Ga)Se2 (CIGS) solar cells are developed on polyimide (PI) foil by using a three‐stage co‐evaporation method. To deposit CIGS on a PI substrate, low temperature deposition process (below 440 °C) is investigated. By optimizing the three‐stage process, power conversion efficiency (PCE) values of 12.1% and 13.6% are obtained at maximum process temperatures of 400 °C and 440 °C, respectively (without anti‐reflection coating). The CIGS absorber deposited at 400 °C is grown with (220)/(204) rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Figure shows capacitive frequency (C–f) spectra of the CIGS devices measured under dark condition with the temperature range of 120–300 K. The capacitance at high frequency mainly represents the response caused by free carrier density, while the capacitance at low frequency represents the response caused by free carrier and deep trap. [ 37,43 ] As shown in Figure 8, the capacitance without OVC device showed larger variation as a function of frequency (Figure 8a), while the capacitance with OVC device displayed smaller variation (Figure 8b). The significant frequency dependence of the without OVC device capacitance demonstrated the higher trap densities within the absorber layer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure shows capacitive frequency (C–f) spectra of the CIGS devices measured under dark condition with the temperature range of 120–300 K. The capacitance at high frequency mainly represents the response caused by free carrier density, while the capacitance at low frequency represents the response caused by free carrier and deep trap. [ 37,43 ] As shown in Figure 8, the capacitance without OVC device showed larger variation as a function of frequency (Figure 8a), while the capacitance with OVC device displayed smaller variation (Figure 8b). The significant frequency dependence of the without OVC device capacitance demonstrated the higher trap densities within the absorber layer.…”
Section: Resultsmentioning
confidence: 99%
“…This result demonstrated that the interface recombination was significantly passivated by the formation of OVC phase. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42] Bandgap grading structure is commonly exhibited by all device types, which takes advantage of the minimum bandgap to increase light absorption and the bandgap grading toward the back interface to facilitate charge collections. [3,4,26] In the BK-CIGS absorber layer, the minimum E c and maximum E v regions are extended from the decreasing tendency of S/(S+Se) and Ga/(Ga+In) ratio. The notch region, which refers to the minimum E g region, extends and the notch depth is reduced throughout the depth of the BK-CIGS film (Figure 1e).…”
Section: Varying Composition Distribution and Bandgap Gradingmentioning
confidence: 99%
“…In general, a bandgap grading structure is suggested in bulk CIGS films with a deep notch point near the surface, as well as increased bandgap at both the top and bottom surfaces to enhance device open-circuit voltage (V oc ) and short-circuit current density (J sc ), respectively. [3,4,26] To further optimize the bandgap grading structure, a wide notch region and a moderately steep gradient are necessarily required to maximize the optical absorption without compromising V oc . [16,25] When an incident light propagates from the pn-junction to the CIGS light absorber, minority carrier electrons generated within the space charge region (SCR) of the pn-junction are subsequently drifted to the electrode by the device electrical field.…”
Section: Introductionmentioning
confidence: 99%